Evaluation of the antidiabetic potential of an isolated hydroalcoholic fraction from the fruit of withania coagulans - Md Waris; Naiyer Shahzad; Saeed Saeed Al-Ghamdi; Showkat Rasool Mir; Tanuja (Wolters Kluwer Medknow Publications, 2021)
The hydro-alcoholic extract of Withania coagulans fruits was investigated for preliminary phytochemical screening and characterized by high-performance thin-layer chromatography. Column chromatography of the hydro-alcoholic extract of W. coagulans eluted with four different combinations of ethyl acetate and methanol yielded four fractions (WCF01, WCF02, WCF03, and WCF04). One of these fractions, WCF02, significantly (P < 0.05) inhibited in vitro α-amylase and α-glucosidase activity with IC50 values of 104.71 μg/mL and 70.79 μg/mL, respectively. WCF02 further reduced blood glucose levels in comparison to control in the starch tolerance test. The extract showed a relative dose-dependent effect. It was observed that none of the extracts could delay the peak blood glucose that was achieved after 60 min of carbohydrate challenge, but these blunted the glycemic peak.